BrasÃlia: tábula rasa e memória (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
Built in exactly 3 years and 17 days, BrasÃlia was inaugurated on April 21, 1960, crowning the development policy of President Juscelino Kubitschek. However, the project to move the capital of Brazil to a new city, to be built in the countryâ€™s uninhabited interior, the central plateau, dates back to distant times. The main buildings in Brasilia were designed by Oscar Niemeyer, an architect who had designed and built the Pampulha complex for Kubitschek between 1940 and 43, in Belo Horizonte. And the urban masterplan was designed by Lucio Costa, winner of a national design competition. Its proposal is based on the demarcation of the territory in two crossed axes in a right angle, alluding to the sign of the cross as the historical gesture of the conquest of an empty territory. In his short description of the idea presented to the judging commission in 1957, Costa recognizes very well the exceptional and somewhat immature aspect of the proposal, since Brasilia would not result from a previous planning of the region, still nonexistent. In his words, â€œthe liberation of access to the competition has, in a sense, reduced the consultation to what really matters, that is, to the urban conception of the city itself, because this will not be a consequence of regional planning, but its origin. The foundation of the city is what will give rise to the further development of the region. It is a deliberate act of possession, of a pathfinder gesture, like in the colonial tradition.â€